2001
DOI: 10.1111/j.1349-7006.2001.tb01175.x
|View full text |Cite
|
Sign up to set email alerts
|

SGLT Gene Expression in Primary Lung Cancers and Their Metastatic Lesions

Abstract: Cancer cells show increased glucose uptake and utilization in comparison with their normal counterparts. Glucose transporters play an important role in glucose uptake. We previously reported the differential gene expression of the GLUT family in primary and metastatic lesions of lung cancer. To investigate the role of Na + /glucose cotransporter (SGLT) genes in cancers, we examined the levels of expression of SGLT1 and SGLT2 genes in primary lung cancers and their metastatic lesions. Ninety-six autopsy samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
2
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 27 publications
2
68
2
3
Order By: Relevance
“…SGLT1, but not SGLT2, mRNA has been identified in distal lung epithelium from adult rats [55,60], and from mouse and human whole-lung tissue [49,56]. BODEGA et al [61] recently identified SGLT protein in type I and II alveolar cells of rat and sheep lung.…”
Section: Glucose Transport In Distal Lung Epitheliummentioning
confidence: 99%
“…SGLT1, but not SGLT2, mRNA has been identified in distal lung epithelium from adult rats [55,60], and from mouse and human whole-lung tissue [49,56]. BODEGA et al [61] recently identified SGLT protein in type I and II alveolar cells of rat and sheep lung.…”
Section: Glucose Transport In Distal Lung Epitheliummentioning
confidence: 99%
“…mRNA (Ishikawa et al 2001), but not protein (Devaskar & de Mello, 1996), and GLUT2 protein (Ito et al 1998) expression have been demonstrated in non-cancerous regions of human lung obtained at autopsy from patients with primary lung carcinomas. A proposed model of glucose homeostasis in human airways is shown in Fig.…”
Section: Glucose Concentrations In Airway Surface Liquidmentioning
confidence: 99%
“…3b, c, however, SGLT1 is heavily expressed in tumor tissue suggesting that SGLT1 similarly contributes to glucose uptake of tumor cells. Expression of SGLT1 in tumor tissue has been demonstrated before [8,13,17,28,31,40,41,63]. In view of the enhanced demand of tumor cells for nutrients and the respective upregulation of glucose and amino acid transport in tumor cells [9,14,15,23,24,27,32,46,64], the upregulation of SGLT1 activity by β-catenin may contribute to the proliferation and survival of tumor cells.…”
Section: Discussionmentioning
confidence: 96%
“…β-catenin sensitive transport systems could well contribute to properties and survival of tumor cells. A variety of tumor cells do express SGLT1 [8,13,17,28,31,40,41,63] and SGLT1-dependent cellular glucose uptake may be required due to the increased energy demand of tumor cells, which is mainly covered by glucose degradation [17]. Moreover, stimulation of the Na + /H + exchanger could alkalinize the cytosol, which would facilitate flux through glycolysis [4].…”
Section: Introductionmentioning
confidence: 99%